SENSE AND THINK MARKETING IMPLICATIONS - Besmandala Napitupulu, Runggu; Lima Krisna, Nandan; Gultom, Lilis Suriani (Dinasti Publisher, 2020)
This research is designed to find out and analyze the implications of sense and think marketing for customer satisfaction and their repurchase intention. The object is a vivo smartphone and respodents are the adult population in Medan who have made a repeat purchase. The analysis technique uses structural equation models. The results showed that marketing sense had a significant effect both on customer satisfaction and repurchase intentions; Think marketing has unsignificant effect on both satisfaction and repurchase intentions; Consumer satisfaction has a significant effect on repurchase intentions; Sense and think marketing simultaneously influence customer satisfaction; Sense marketing, think marketing, and satisfaction simultaneously effect on repurchase intentions for vivo smartphones in Medan.